PENINGKATAN HASIL BELAJAR MATERI NILAI MATA UANG MELALUI PENERAPAN METODE ROLE PLAYING PADA SISWA KELAS II UPT SD NEGERI NGAMPELREJO - Alfiati, Rolis; Melani Yosafa, Eka; Zuhdi, Ulhaq; Riani, Riani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This classroom action research aims to improve students learning outcomes in mathematics on the topic of currency values using the role-playing method, which consists of four stages: planning, action, observing, and reflecting. The research was conducted in the second grade of UPT SD Negeri Ngampelrejo involving 25 students. Data collection instruments used were observation and learning outcome tests. The results showed an improvement in the learning outcomes of second-grade students at UPT SD Negeri Ngampelrejo, evidenced by the learning outcomes in the first cycle reaching 64% of the minimum competency criteria (KKM) with an average score of 67.8, and further increasing in the second cycle with a percentage of 96% and an average score of 87.6. These findings indicate that the application of the role-playing method effectively improves learning outcomes on the topic of currency values in the second grade of UPT SD Negeri Ngampelrejo.